Novel multifunctional platinum nanodendrites as theranostic agents in cancer imaging and radiotherapy treatment - Anuar, Muhammad Afiq Khairil (2021)
High-Z nanoparticles have been studied over the years as a potential radio-theranostic agent due to their high X-ray absorption and good pharmacokinetic properties. However, only a few platinum-based agents have been reported in the literature, despite its wide usage in chemotherapy (i.e., cisplatin). Thus, this work aims to study platinum nanoparticles, Platinum Nanodendrites (PtND), as a novel theranostic agent. The PtNDs fabricated in this work possessed a dendritic shape with a negatively charged surface. Four PtND sizes were prepared for theranostic evaluations (29 nm, 36 nm, 42 nm, and 52 nm). In-vitro biocompatibility assessment revealed that the PtNDs of all sizes were non-cytotoxic for the particle concentration of up to 0.1 mM. Furthermore, the PtNDs’ toxicity also depended on PtNDs’ size, cell type, and incubation period. The theranostic evaluation of PtNDs was separated into diagnostic and radiotherapy sections. The diagnostic evaluation was performed with the maximum available PtND concentration, 1.0 mM, to maximize their image contrast in X-ray images. The PtNDs of different sizes were compared with the commercial iodinated contrast agent in three X-ray modalities (CT, fluoroscopy, and planar X-ray). The result in all imaging systems evidenced better attenuation of PtNDs over iodinated contrast agent at equivalent concentration. The contrast enhancement is also size-dependent, where larger PtNDs exhibited higher X-ray attenuation than the smaller ones. The radiotherapy evaluation involved a study on the radiosensitization effects of PtNDs in three different types of radiotherapy: 6 MV photon radiotherapy, 6 MeV electron beam therapy, and 150 MeV proton beam therapy. HeLa cells were treated with 0.1 mM of PtNDs of different sizes and subjected to increasing radiation doses. The clonogenic assay evaluations revealed that the PtNDs successfully enhanced the radiosensitivity of HeLa cells, depending on the particle size and types of radiotherapy. The maximum radiosensitization effect was observed in the combination of 29 nm PtNDs with PhT (SER=2.54). 36 nm and 42 nm PtNDs produced the highest radiosensitization in PrT (SER=1.38) and EBT (SER=1.83), respectively. DCF assay assessment shows that the ROS induced by the PtND-radiation combinations may not be the major determining factors that catalyse the PtNDs’ radiosensitization effect. In conclusion, this work has successfully developed and characterized the theranostic potential of PtNDs. This study provides a platform for theranostic multimodal approaches in diagnostic imaging and radiotherapy to improve cancer treatment efficacy and outcomes.